Assessing prospective biology teachers’ knowledge and perceptions regarding basic teaching skills through revised Bloom’s taxonomy - Eko Sri Wahyuni; T. Titin; Mas Akhbar Faturrahman; Dimas Ananda Virda; Dian Wahyuningsih (JPBI (Jurnal Pendidikan Biologi Indonesia), 2026)
Background: Prospective biology teachers often struggle to acquire an adequate level of knowledge and perceptions regarding basic teaching skills, resulting in limitations in applying them. Objectives: This research aims to assess the knowledge and perceptions of prospective biology teachers regarding basic teaching skills at Universitas Tanjungpura, one of the leading universities in West Kalimantan that offers the Biology Education study program. Methods: This research is descriptive quantitative, involving 68 students, selected through total sampling. The instruments were a test and a questionnaire that integrated the revised Bloom’s taxonomy and eight basic teaching skills, assessed for feasibility by five experts. Results: The results from the test revealed an average percentage of correct answers of 87.55% (good) and a grade of 80.04 (very good). The questionnaire showed an average percentage of 82.01% (proficient). These findings indicate that although the results show adequate mastery of basic teaching skills based on knowledge and perceptions, it has not reached the maximum achievement and needs to be optimized. Conclusion: It is necessary to improve the design of the Basic Biology Teaching Skills course. The course should not only simulate basic teaching skills but also optimize their achievement across each cognitive dimension of the revised Bloom’s taxonomy.